2018
DOI: 10.1024/0301-1526/a000688
|View full text |Cite
|
Sign up to set email alerts
|

Loco-regional versus general anaesthesia for elective endovascular aneurysm repair – results of a cohort study and a meta-analysis

Abstract: Local and/or regional anaesthetic techniques may be advantageous over GA in elective EVAR, as indicated by reduced perioperative mortality and morbidity and a shorter hospital stay. Considering the current level of evidence, LA or RA should be considered in selected patients. Further clinical research is required to provide high level evidence on the optimal anaesthetic technique in EVAR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 21 publications
0
8
0
1
Order By: Relevance
“…Indeed, many studies described the use of CSA in high-risk patients undergoing cardiac, vascular, orthopedic, pelvic, and abdominal surgery who would be considered unlikely to survive general anesthesia [ 11 , 12 ]. This method provides significantly improved hemodynamic control, avoids invasive airway management, enhances intraoperative analgesia, and allows the maintenance of a postoperative analgesia with superior efficiency and minimal effect on mental status, carrying a considerable reduction in major postoperative complications compared to GA [ [3] , [4] , [5] ], particularly in the elderly. TCSA reinforces all these benefits in abdominal surgery due to its selective spinal block allowing a rapid onset of action and a reduced dose of local anesthetic required [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, many studies described the use of CSA in high-risk patients undergoing cardiac, vascular, orthopedic, pelvic, and abdominal surgery who would be considered unlikely to survive general anesthesia [ 11 , 12 ]. This method provides significantly improved hemodynamic control, avoids invasive airway management, enhances intraoperative analgesia, and allows the maintenance of a postoperative analgesia with superior efficiency and minimal effect on mental status, carrying a considerable reduction in major postoperative complications compared to GA [ [3] , [4] , [5] ], particularly in the elderly. TCSA reinforces all these benefits in abdominal surgery due to its selective spinal block allowing a rapid onset of action and a reduced dose of local anesthetic required [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although general anesthesia (GA) is routinely used for major abdominal surgery, it is accompanied by significant morbidity and mortality, especially in elderly patients suffering from multiple severe systemic diseases (American Society of Anesthesiologists [ASA] classification III or above) [ 2 ]. Accordingly, regional anesthesia, particularly neuraxial blockade, has gained popularity as an effective and safe technique that might provide improved outcomes in terms of perioperative morbidity and mortality compared to GA, although conclusive, long-term evidences are still missing [ [3] , [4] , [5] ]. Spinal anesthesia and epidural anesthesia are the 2 main types of neuraxial blockade and have been shown to decrease respiratory and cardiac complications [ 3 , 6 ] and the neuroendocrine stress response [ 7 ], to improve effective pain control [ 8 ], to promote return of gastrointestinal function [ 8 , 9 ], to protect against thromboembolic events [ 10 ], and to facilitate early patient mobilization.…”
Section: Introductionmentioning
confidence: 99%
“…Although eEVARs can be conducted under local or regional anesthesia, general anesthesia is used for EVAR in approximately 90% of cases, according to a large Vascular Quality Initiative study [28]. This is likely attributable to conflicting reports regarding the superior safety of loco-regional anesthetic techniques for EVAR [29,30]. Instead, we tested the PPV of OHIP billing codes, which are submitted by the operating physician, and thus less likely to be mistakenly miscoded.…”
Section: Discussionmentioning
confidence: 99%
“…Regional anesthesia is used worldwide by anesthesiologists to avoid the risks of general anesthesia. Despite previous controversial reports, many studies support the advantages of regional anesthesia over general anesthesia [20][21][22] . A study in patients who underwent elective endovascular repair found that perioperative death in the regional anesthesia group was significantly lower than in the general anesthesia group (0.5 vs 4.3%, p = 0.007) 21 .…”
Section: Continuesmentioning
confidence: 99%
“…Despite previous controversial reports, many studies support the advantages of regional anesthesia over general anesthesia [20][21][22] . A study in patients who underwent elective endovascular repair found that perioperative death in the regional anesthesia group was significantly lower than in the general anesthesia group (0.5 vs 4.3%, p = 0.007) 21 . A systematic review and meta-analysis that compared general anesthesia and neuraxial anesthesia in hip fracture patients showed that neuraxial anesthesia significantly reduced the inhospital mortality rate (OR 0.85, 95% CI 0.76-0.95), p = 0.004) 20 .…”
Section: Continuesmentioning
confidence: 99%